Pengaruh Model Pembelajaran kooperatif Tipe Student Teams Achievement Division Terhadap Hasil Belajar Kognitif Siswa - Yulia hidayatul Rohmah; Ana Naimatul Jannah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This study aims to determine the effect of the cooperative learning model of the Student Teams Achievement Division (STAD) type on the cognitive learning outcomes of class V UPTD SDN 2 Telang. This research is a quantitative research with experimental research type, the design used is Pre-Experimental Design with One-group Pre-test-Posttest Design. Sampling using a population sample technique. The sample used amounted to 18 students. Data collected using pre-test and post-test questions. The results of the research show a matter of pre-test and post-test. The results showed: 1) The STAD Learning Model has a significant effect with the result tcount 20.151 greater than ttable 1.739, based on the testing criteria if the value of tcount > ttable, then H0 is rejected and Ha is accepted which means that there is an influence of the student team learning model on achievement division on learning outcomes student cognitive. 2) the implementation of learning themes 9 sub-themes 4 with the learning model of student group distribution of achievements carried out with very good criteria with an average score of 95.37%